Association between Poststroke Depression and Psychological Crisis: A Retrospective Cross-Sectional Study. (27th January 2021) - Hsieh, Han-Chin; Yang, Pei-Jin; Huang, Yu-Chi; Lee, Yan-Yuh; Yang, Tsung-Hsun; Wu, Szu-Ying; Chen, Po-Cheng
Abstract : Objective . To investigate the association between poststroke depression (PSD) and psychological crisis in patients who have experienced a stroke within 6 months. Methods . This was a retrospective cross-sectional study that enrolled patients within 6 months after stroke onset. The investigators reviewed medical charts to obtain patients' baseline characteristics, and a psychologist evaluated each patient for depression using the Taiwanese Depression Questionnaire (TDQ) and for psychological crisis using the Triage Assessment System (TAS). A generalized linear model (GLM) was used to analyze the association between the results of the TDQ and TAS. Results . Ninety-seven patients with stroke were included. Age (p = 0.003 ), time since onset of stroke (p = 0.041 ), diabetes mellitus (p = 0.004 ), hypertension (p = 0.016 ), heart disease (p = 0.005 ), and TDQ score were significantly different between the hemorrhagic stroke group and the ischemic stroke group. The TDQ score was significantly lower in the hemorrhagic stroke group (p = 0.012 ). The TDQ score was associated with the TAS total score and each domain score, and the presence of heart disease was associated with poorer TAS score in the behavioral domain (p = 0.016 ). Conclusion . PSD is likely an important component of psychological crisis in stroke patients. For clinicians, a comprehensive psychologic evaluation is necessary to optimize treatment.